2017
DOI: 10.1111/ppl.12562
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of strategies for escaping reactive oxygen species production within photosystem I among land plants: P700 oxidation system is prerequisite for alleviating photoinhibition in photosystem I

Abstract: In land plants, photosystem I (PSI) photoinhibition limits carbon fixation and causes growth defects. In addition, recovery from PSI photoinhibition takes much longer than PSII photoinhibition when the PSI core-complex is degraded by oxidative damage. Accordingly, PSI photoinhibition should be avoided in land plants, and land plants should have evolved mechanisms to prevent PSI photoinhibition. However, such protection mechanisms have not yet been identified, and it remains unclear whether all land plants suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
76
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 67 publications
(165 reference statements)
5
76
0
Order By: Relevance
“…Furthermore, we also found that inducing Y(ND) under illumination is a major mechanism to lower the risk of PSI photoinhibition in photosynthetic organisms (Shimakawa et al , , Takagi et al ). We named this new mechanism, for avoiding ROS production under illumination, the ‘P700 oxidation system’ (Shimakawa et al , , Takagi et al ).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Furthermore, we also found that inducing Y(ND) under illumination is a major mechanism to lower the risk of PSI photoinhibition in photosynthetic organisms (Shimakawa et al , , Takagi et al ). We named this new mechanism, for avoiding ROS production under illumination, the ‘P700 oxidation system’ (Shimakawa et al , , Takagi et al ).…”
Section: Introductionmentioning
confidence: 94%
“…That is, maintaining Y(ND) lowers the quantum yield of ROS production in PSI during photosynthesis. In a subsequent study, we found that photosynthetic organisms from cyanobacteria higher plants possess and develop various mechanisms to induce P700 + during photosynthesis (Shaku et al , Shimakawa et al , Takagi et al ). Furthermore, we also found that inducing Y(ND) under illumination is a major mechanism to lower the risk of PSI photoinhibition in photosynthetic organisms (Shimakawa et al , , Takagi et al ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In photosynthetic electron transport, PSII is the main source of singlet oxygen ( 1 O 2 ) while superoxide (O 2 •− ) is mainly generated at PSI. However, PSI may also generate 1 O 2 when illuminated with repetitive short light pulses of high intensity (Takagi et al ). The molecular mechanism of 1 O 2 generation in PSI is unknown but it has been demonstrated that 1 O 2 in PSII is generated by charge recombination reactions of the primary radical pair, yielding the triplet state of chlorophyll.…”
mentioning
confidence: 99%